IN-VITRO CAPACITATION OF BOVINE SPERMATOZOA BY MEASURING PENETRATING POTENTIAL - SINGH, S; GUPTA, H P; MISHRA, A K; KUMAR, A (The Indian Journal of Animal Reproduction, 2023)
Penetrating potential of bovine spermatozoa, capacitated in vitro, w studied in terms of sperm penetratio distance (SPD) to determine the suitable combination of caffeine concentration and incubation period foroptimu capacitation. The capacitation was induced in sperm TALP (Tyrode’S albumin, lactate and pyruvate) medium containing 0, 5, 10 and 20 mM caffeine at 39 °C for 0, 30, 60 and 90 min. The c pacitated spermatozoa were subjected to penetration in 2% polyacrylamide gel and SPD was measured. The maximum SPD of 19.35±0.50 mm /hr was recorded at 20mM caffeine with 90 min incubation period indicating this period and concentration combination as the most effective enhancer of in vitro capacitation of bovine spermatozoa.